Pengaruh Pembelajaran Fisika Menggunakan Direct Insruction (Di) melalui Pemodelan Korektif Terhadap Hasil Belajar Fisika Siswa Kelas Viii SMPN 2 Labuhan Haji Tahun Ajaran 2013/2014 - Zaini Zaini; Sutrio Sutrio; Gunawan Gunawan (Department of Physics Education, Universitas Mataram, 2015)
This research is research experiments with a purpose to knows the effect of physics learning using direct instruction (DI) throught corrective models toward result of study physics on grade VIII SMPN 2 Labuhan Haji in academic year 2013/2014. This research using the Nonequivalent Multiple Groups Pretest Posttest Design. The technique to obtain the sample using purposive sampling technique. The population in this research is all the Classes VIII SMPN 2 Labuhan Haji. Whereas itÃ¢â¬â¢s Sample obtained by the student on Grade VIII E as the experiment class and VIII F as the control class. The data result studying analyzed by t-test two tail using formulas separated variance. From the result of research obtained from materials of pressure and vibration and wave is tcount = 2,646 and tcount =6,004, whereas ttable = 2,012 on degree of free is 56 with standard significant is 5%. BecauseÃÂ tcount on preesure materials and vibration and wave materials biger than ttable ,so Ho will be rejected and Ha will be accepted which indicate that there are effects of physics learning usingÃÂ direct instruction (DI) throught corrective models toward the result studying physics on grade VIII SMPN 2 Labuhan Haji in academic year 2013/2014.